Temporal trends in lung cancer mortality and years of life lost in Wuhan, China, 2010-2019 - Yan, Yaqiong; Ma, Yudiyang; Li, Yimeng; Zhang, Xiaoxia; Zhao, Yuanyuan; Yang, Niannian; Yu, Chuanhua (Frontiers in Oncology, 2022)
Objective: Lung cancer is responsible for millions of deaths yearly, and its burden is severe worldwide. This study aimed to investigate the burden of lung cancer in the population of Wuhan based on the surveillance data from 2010 to 2019. Methods: Data of this study was obtained from the Mortality Register System established by the Wuhan Center for Disease Control and Prevention. The study systematically analyzed the burden of lung cancer deaths in the population of Wuhan and its 13 administrative regions from 2010 to 2019 via the Joinpoint regression models, Age-Period-Cohort (APC) models, and decomposition analysis. Results: This study found upward and downward trends in ASMR and ASYLLR of lung cancer from 2010 to 2019. The corresponding estimated annual percentage change (EAPC) were 1.00% and -1.90%, 0.60%, and -3.00%, respectively. Both population aging (P<0.01) and population growth (P<0.01) aggravated (Z>0) lung cancer deaths in the Wuhan population. Population aging (Z=3.94) was proved to be the most severe influence factor on lung cancer deaths. In APC models, lung cancer mortality tended to increase with age for both sexes in Wuhan, peaking at the 85-89 age group; The period effects illustrated continuous decreasing trends, and the cohort effects indicated that the risk of lung cancer death was highest among those born between 1955 and 1965, at 1.23 (males) and 1.13 (females). Among all administrative districts in Wuhan, the ASMR of lung cancer in the Xinzhou District has remained the highest over the study period. Conclusions: The burden of lung cancer deaths remained a public health challenge in Wuhan as the population was aging and population growth. In addition, surveillance of lung cancer deaths contributed to valuable insights into lung cancer control and prevention.